การยึดติดระหว่างซี่ฟันปลอมสำเร็จรูปชนิดต่างๆที่ได้รับการปรับพื้นผิวด้วยสารไซเลนกับอะคริลิกฐานฟันปลอมชนิดบ่มด้วยความร้อน - พีรานุช ประหยัดทรัพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The aim of this article was to studytensile bond strength between silane modified acrylic denture teeth and heat-cured denture base. According to polymer characteristics, the denture teeth studied were as follows;1) linear methyl methacrylate 2) partially cross-linked acrylic with PMMA powders 3) highly cross-linked polymethyl methacrylate with colloidal silica 4) interpenetrating network. The bonding area was treated with 0,0.1, 1, 2 M gamma methacryloxypropyltrimethoxy silane solution. All specimen were prepared according to the conventional denture fabrication and shaped into miniumbell shape with 2 mm in thickness and loading area of 2x3 mm. Before testing all specimen were placed in 37 degree celcius distilled water fo 24 hours. All test were performed on Universal testing machine (Instron, Model 8872) with cross head-speed of 1 mm/min. The esults, analysed by 2-way ANOVA and multiple comparison, revealed interpenetrating network denture teeth showed the highest tensile bond strength and highly cross-linked polymethyl methacrylate with colloidal silica showed the lowest in O M group. Among siloane modified group, linear methyl methacrylate denture teeth showed significant increase in tensile bond strength while the other showed no significant differences.